Perlambatan Ekonomi Global Dan Tantangan Ekspor Indonesia - Ririn Mely Anggraini; Sriyagis; Maria Jesi Klarita Maharia; Syafaatul Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the impact of the global economic slowdown on Indonesia’s export performance from a macroeconomic perspective. Global uncertainty caused by inflation, geopolitical conflicts, supply chain disruptions, and high interest rate policies has weakened international trade activities and reduced demand for exports from developing countries, including Indonesia. This research uses a qualitative approach with a literature review method by examining scientific journals, government publications, and reports from international institutions published within the last five years. The analysis process was carried out through the identification of global economic trends, examination of Indonesia’s export performance, and interpretation of the implications of export slowdown on national economic stability. The results indicate that the global economic slowdown has reduced demand for Indonesia’s export commodities, especially in mining, plantation, and manufacturing sectors. In addition, fluctuations in commodity prices, exchange rate instability, and increasing trade protectionism have become major challenges for Indonesia’s export competitiveness. The study concludes that export diversification, industrial downstreaming, strengthening industrial competitiveness, and expanding international trade cooperation are essential strategies to maintain Indonesia’s economic resilience amid global uncertainty.